THE ROLE OF ARTIFICIAL INTELLIGENCE (AI) IN ENGLISH LANGUAGE TEACHING IN THE ERA OF GLOBALIZATION: A LITERATURE REVIEW - Ela Nurainisah; Septika Ariyanti; Defy Gustianing (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2025)
This study aims to review the impact and challenges of the application of Artificial Intelligence (AI) in English language teaching in the era of globalization. The background of this review is based on the significant digital transformation in language teaching methods triggered by technological advances, especially AI which offers a more adaptive and interactive approach to learning. The method used is a literature review with a qualitative descriptive approach to various scientific publications in the last 10 years obtained from databases such as Google Scholar, ResearchGate, and ScienceDirect. Literature review shows that AI can expand access to rich learning resources, and support adaptive learning. However, negative impacts and challenges such as reducing the role of the teacher as a critical learning facilitator, ethical issues, teacher readiness and over-reliance have also emerged significantly. Therefore, although AI has great potential in revolutionizing ELT, its application must consider ethical principles, human resource readiness, and the balance between technology and human touch in the learning process.